2008
DOI: 10.3319/tao.2008.19.4.347(images)
|View full text |Cite
|
Sign up to set email alerts
|

Late Quaternary Planktic Foraminifer Fauna andMonsoon Upwelling Records from the Western South China Sea, Near the Vietnam Margin (IMAGESMD012394)

Abstract: Marine sediment core MD012394 from the Vietnam coastal upwelling area in the western South China Sea was investigated in order to reconstruct the last Quaternary monsoon upwelling based on planktic foraminifer fauna assemblages and fauna-based sea surface temperature (SST) estimates. The age model of core MD012394 was constructed using oxygen isotope stratigraphy of the planktic foraminifer G. sacculifer, with 10 accelerator mass spectrometry (AMS) 14 C dating of planktic foraminifers from the sediment sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…South China Sea sediments provide some information on fluctuations in the intensity of the EAWM. A number of micropaleontological, sedimentological, and geochemical proxies for the EAWM have been proposed (Jian and Tian, 2009), such as surface productivity, winter SST, and clay mineralogy in the South China Sea (Wang et al , 1999; Jian et al , 2001; Zhao et al , 2006; Yu et al , 2008; Shiau et al , 2008). High productivity related to enhanced upwelling and low SST during winter in the northern South China Sea occurs when the EAWM is more intense.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…South China Sea sediments provide some information on fluctuations in the intensity of the EAWM. A number of micropaleontological, sedimentological, and geochemical proxies for the EAWM have been proposed (Jian and Tian, 2009), such as surface productivity, winter SST, and clay mineralogy in the South China Sea (Wang et al , 1999; Jian et al , 2001; Zhao et al , 2006; Yu et al , 2008; Shiau et al , 2008). High productivity related to enhanced upwelling and low SST during winter in the northern South China Sea occurs when the EAWM is more intense.…”
Section: Resultsmentioning
confidence: 99%
“…High productivity related to enhanced upwelling and low SST during winter in the northern South China Sea occurs when the EAWM is more intense. The proxy records in the South China Sea (Jian et al , 2001; Zhao et al , 2006; Yu et al , 2008; Shiau et al , 2008) indicate that the intensity of the EAWM is enhanced during periods of low summer insolation.…”
Section: Resultsmentioning
confidence: 99%
“…It is evident that more records and more novel approaches such as these are needed to resolve questions regarding the relationship and phases of the winter and summer monsoons. Yu et al (2008) reported planktonic foraminiferal assemblage and SST records of the last 135 kyr for core MD012394 from the Vietnam coastal upwelling area in the southwestern SCS, and they focused their discussion on summer monsoon variability. Using a Q-mode factor analysis of the fauna abundance data, Yu et al (2008) found that the relative abundance of G. inflata (Factor 3) can be used as a summer monsoon proxy.…”
mentioning
confidence: 99%
“…Yu et al (2008) reported planktonic foraminiferal assemblage and SST records of the last 135 kyr for core MD012394 from the Vietnam coastal upwelling area in the southwestern SCS, and they focused their discussion on summer monsoon variability. Using a Q-mode factor analysis of the fauna abundance data, Yu et al (2008) found that the relative abundance of G. inflata (Factor 3) can be used as a summer monsoon proxy. High loadings of this summer proxy were recorded around 11, 33, 59, and 83 ka when the local summer insolation was near the maximum.…”
mentioning
confidence: 99%